Pendampingan Pengelolaan Usaha Mikro Kecil Dan Menengah (UMKM) Di Masa Pandemi Corona Virus Disease (Covid-19) Di Lembang Ratte Talonge Kecamatan Saluputti - Rati Pundissing; Chrismesi Pagiu; Dwibin Kannapadang; Dian Intan Tangkeallo; Randi Tangdialla (BADAN PENERBIT STIEPARI PRESS, 2021)
Community service is one part of the tridharma of higher education that must be carried out. The Covid-19 pandemic has had a major impact on various sectors, especially the economic sector, one of which is MSMEs. For this reason, community service in the form of assistance in managing MSMEs is considered very necessary. The aim of implementing the Community Service for Management of Micro, Small and Medium Enterprises (MSMEs) during the Corona Virus Disease (Covid-19) Pandemic in Lembang Ratte Talonge, Saluputti District is to help resolve MSME problems in developing businesses through training in business management in the Covid-19 Era, financial management and capital in Lembang Ratte Talonge, Saluputti District. Apart from that, this community service also aims to improve the skills of business actors in managing MSMEs in Lembang Ratte Talonge, Saluputti District.